2001
DOI: 10.1037/0096-1523.27.5.1197
|View full text |Cite
|
Sign up to set email alerts
|

Capture of attention in selective frequency listening.

Abstract: Four signal-detection experiments demonstrated robust stimulus-driven, or exogenous, attentional processes in selective frequency listening. Detection of just-above-threshold signal tones was consistently better when the, signal matched the frequency of an uninformative cue tone, even with relatively long cue-signal delays (Experiment 1) or when as few as 1 in 8 signals were at the cued frequency (Experiment 2). Experiments 3 and 4 compared performance with informative and uninformative cues. The involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 62 publications
3
46
2
Order By: Relevance
“…In some cases the expected frequency is the same throughout the experiment, and in others is established by cues of various types presented before each trial (Hafter, Schlauch, & Tang, 1993;Hübner & Hafter, 1995;Macmillan & Schwartz, 1975;Scharf, Quigley, Aoki, Peachey, & Reeves, 1987;Schlauch & Hafter, 1991). These cues need not be informative in order for frequency facilitation to occur, which suggests that exogenous or automatic as well as endogenous or controlled mechanisms may be involved (Green & McKeown, 2001). …”
Section: Attention To Auditory Frequency-mentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases the expected frequency is the same throughout the experiment, and in others is established by cues of various types presented before each trial (Hafter, Schlauch, & Tang, 1993;Hübner & Hafter, 1995;Macmillan & Schwartz, 1975;Scharf, Quigley, Aoki, Peachey, & Reeves, 1987;Schlauch & Hafter, 1991). These cues need not be informative in order for frequency facilitation to occur, which suggests that exogenous or automatic as well as endogenous or controlled mechanisms may be involved (Green & McKeown, 2001). …”
Section: Attention To Auditory Frequency-mentioning
confidence: 99%
“…In other words, there was no cue validity of the prime. Thus, the participant gains no advantage by adopting an explicit, endogenous strategy to attend to the primed range (also see Green & McKeown, 2001;Mondor, Hurlburt, & Gammell, 2003).…”
Section: Attention To Auditory Frequency-mentioning
confidence: 99%
“…It is known that listeners can effectively monitor a particular frequency, and a pure tone cue can direct listeners to a particular frequency (e.g. Green & McKeown, 2001). Perhaps, then, attention wanders from the standard tone frequencies at longer RIs, leading to a decline in discriminatory accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…However, one previous study has provided evidence of involuntary attention to frequency in cued signal detection tasks: In a series of experiments conducted by Green and McKeown (2001), detection performance with uninformative cues was consistently better on the occasional trials when the target matched the frequency of the cue (valid trials) than on the remaining trials when it was at one or other distant frequency (invalid trials). One finding arose from direct comparisons of performance with uninformative versus informative cues.…”
mentioning
confidence: 98%
“…This is much longer than the duration of the facilitatory effects of uninformative frequency cues found in the experiments of Mondor and colleagues, and of the involuntary effects typically reported in studies of spatial attention in both vision and audition. Green and McKeown (2001) suggested that the involuntary effects of cues on detection performance could be explained in terms of the influence of memory traces of previously presented stimuli. Cowan (1984) identified two phases of auditory sensory memory: a brief afterimage lasting a few hundred milliseconds, and a more processed memory preserving sensory features for up to 10 sec or more, corresponding closely to what has been termed synthesized auditory memory (Massaro, 1975).…”
mentioning
confidence: 99%